Human Epididymis Protein 4 Promotes Events Associated with Metastatic Ovarian Cancer via Regulation of the Extracelluar Matrix - Ribeiro, Jennifer R.; Gaudet, Hilary M.; Khan, Mehreen; Schorl, Christoph; James, Nicole E.; Oliver, Matthew T.; DiSilvestro, Paul A.; Moore, Richard G.; Yano, Naohiro (Frontiers in Oncology, 2018)
Human epididymis protein 4 (HE4) has received much attention recently due to its diagnostic and prognostic abilities for epithelial ovarian cancer. Since its inclusion in the Risk of Ovarian Malignancy Algorithm (ROMA), studies have focused on its functional effects in ovarian cancer. Here, we aimed to investigate the role of HE4 in invasion, haptotaxis, and adhesion of ovarian cancer cells. Furthermore, we sought to gain an understanding of relevant transcriptional profiles and protein kinase signaling pathways mediated by this multifunctional protein. Exposure of OVCAR8 ovarian cancer cells to recombinant HE4 (rHE4) promoted invasion, haptotaxis toward a fibronectin substrate, and adhesion onto fibronectin. Overexpression of HE4 or treatment with rHE4 led to upregulation of several transcripts coding for extracellular matrix proteins, including SERPINB2, GREM1, LAMC2, and LAMB3. Gene ontology indicated an enrichment of terms related to extracellular matrix, cell migration, adhesion, growth, and kinase phosphorylation. LAMC2 and LAMB3 protein levels were constitutively elevated in cells overexpressing HE4, and were upregulated in a time-dependent manner in cells exposed to rHE4 in the media. Deposition of laminin-332, the heterotrimer comprising LAMC2 and LAMB3 proteins, was increased in OVCAR8 cells treated with rHE4 or conditioned media from HE4-overexpressing cells. Enzymatic activity of matriptase, a serine protease that cleaves laminin-332 and contributes to its pro-migratory functional activity, was enhanced by rHE4 treatment in vitro. Proteomic analysis revealed activation of focal adhesion kinase signaling in OVCAR8 cells treated with conditioned media from HE4-overexpressing cells. Focal adhesions were increased in cells treated with rHE4 in the presence of fibronectin. These results indicate a direct role for HE4 in mediating malignant properties of ovarian cancer cells, and validate the need for HE4-targeted therapies that will suppress activation of oncogenic transcriptional activation and signaling cascades.